An Alternative Treatment Against Acanthocephala (Prosthenorchis elegans) in Captive Squirrel Monkeys (Saimiri sciureus) in Mexico - José Zárate-Ramos, J. J; Gómez-Garza, M. A; Rodríguez-Tovar, L. E; Escareño, J. Hernández; Contreras-Lozano, J. A (The Journal of parasitology, 2018)
We provide the first report of Acanthocephala (Prosthenorchis elegans) in Mexican non-human primates. There has been no known treatment against this parasite except for surgical removal, and this has been relatively ineffective because of the small juveniles. We report the presence of P. elegans in a captive breeding colony of squirrel monkeys (Saimiri sciureus) in Mexico, and we describe a successful treatment protocol. Treatment involved 2 steps: oral administration of the drugs loperamide chlorhydrate (0.5 mg/0.9 kg/3 days) and niclosamide (0.2 mg/0.9 kg/3 days) followed by surgical removal of adult worms from the intestine. Fecal examination during treatment revealed live adults but no living juveniles and no eggs. Surgery after 1 wk of treatment revealed the presence of adults and an absence of juvenile parasites. All adults were physically extracted during the surgery. All subjects recovered from surgery within 1 wk.